A multifactorial explanation of youth unemployment and the special case of Austria. (January 2015) - Tamesberger, Dennis
Abstract: One of the biggest challenges currently facing European society is the dramatically high level of youth unemployment. Commonly, political solutions and strategies can be found in those countries that have been able to keep youth unemployment low in spite of the financial and economic crises. Austria is such a case. On the basis of European Union Member State data, the article gives a multifactorial explanation of youth unemployment and asks whether these factors can explain relatively low youth unemployment in Austria. With the country's "youth safety net" presented in detail, it is shown that active labour market policy reduces youth unemployment in Austria. The article also points out the limitations of cross‐country comparisons of youth unemployment rates and proposes the use of a greater number of indicators. Finally, the article argues for economic policies to stimulate demand, which have to be based on a political and social commitment to full employment.